UG3 Connect email – 8 years' experience of an email clinic in an hiv outpatient setting. (8th June 2017) - Beksinska, Alicja; Nixon, Eileen; Weir, Gemma; Churchill, Duncan; Whetham, Jenny
Abstract : Introduction: With advances in HIV therapy, many people are living longer healthier lives. Simultaneously our cohorts are ageing with 42% of individuals locally aged over 50. Our service looked for innovative ways of reducing visits for stable patients while increasing capacity to manage complex patients. In 2008 we introduced an email service whereby patients are seen once a year with interim results checked and emailed to them. We report on a review of the Connect email service. Methods: Individuals who had ever registered with the email service and their current status were identified from our prospective clinical database. Reasons for 'exiting' or 'pausing' the service were identified by a case notes review. A service evaluation was carried out via staff and patient surveys. Results: Since October 2008, 888 individuals have registered with our email service: 89.8% male (n=797); median age 48 (range 22–84). At the time of review (Oct 2016) 550 (550/2370 = 23% of total cohort) were under active email follow-up. In eight years, 171 (19.3%) have 'exited' the email service - reasons included: co-morbidities (46.2%); ARV switch/start (18.7%); patient choice (12.9%) and non-attendance/adherence (11.1%). A further 167(18.8%) has been 'paused', mainly due to co-morbidities (58.1%); ARV switch/start (20.4%) and research (16.2%). Non-attendance/adherence was more common in younger patients while co-morbidities predominated among older patients (aged >50). In the staff survey, barriers for enrolling patients on Connect included 'difficulty letting go' of regular appointments, email access and confidentiality concerns. Discussion: As the email service is an integral part of HIV care in our unit, understanding why patients leave Connect and barriers to enrolment will enable continued effectiveness of the service.